From monasteries to hospitals: Buddhist and Islamic medical traditions - Mohamed Ashath, Mohamed Shafeen (Study Buddhism, 2026)
The historical narratives of Buddhist and Islamic societies extend far beyond mere accounts of political dominion and religious debate; they are fundamentally linked with the quest for healing both the mind and body. From the early monastic medical facilities in India and Sri Lanka to the magnificent hospitals of Abbasid Baghdad and Ottoman Constantinople, healthcare establishments served as vital hubs of education, empathy, and community service. While these traditions are frequently examined separately, they actually demonstrate a complex network of scholarly interaction and common humanitarian principles. Across the ages, Buddhist and Islamic medical practices have evolved along interconnected paths, exhibiting ongoing and productive knowledge exchange. Accordingly, medicine has always served as a bridge across many religious and cultural domains, facilitating contact via the common human experiences of illness and recovery.